A genome-wide genetic linkage map and reference quality genome sequence for a new race in the wheat pathogen Pyrenophora tritici-repentis - Kariyawasam, G.K.; Wyatt, N.; Shi, G.; Liu, S.; Yan, C.; Ma, Y.; Zhong, S.; Rasmussen, J.B.; Moolhuijzen, Paula; Moffat, Caroline; Friesen, T.L.; Liu, Z. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Pyrenophora tritici-repentis is an ascomycete fungus that causes tan spot of wheat. The disease has a worldwide distribution and can cause significant yield and quality losses in wheat production. The fungal pathogen is homothallic in nature, which means it can undergo sexual reproduction by selfing to produce pseudothecia on wheat stubble for seasonal survival. Since homothallism precludes the development of bi-parental fungal populations, no genetic linkage map has been developed for P. tritici-repentis for mapping and map-based cloning of fungal virulence genes. In this work, we created two heterothallic strains by deleting one of the mating type genes in each of two parental isolates 86–124 (race 2) and AR CrossB10 (a new race) and developed a bi-parental fungal population between them. The draft genome sequences of the two parental isolates were aligned to the Pt-1C-BFP reference sequence to mine single nucleotide polymorphisms (SNPs). A total of 225 SNP markers were developed for genotyping the entire population. Additionally, 75 simple sequence repeat, and two gene markers were also developed and used in the genotyping. The resulting linkage map consisted of 13 linkage groups spanning 5,075.83 cM in genetic distance. Because the parental isolate AR CrossB10 is a new race and produces Ptr ToxC, it was sequenced using long-read sequencing platforms and de novo assembled into contigs. The majority of the contigs were further anchored into chromosomes with the aid of the linkage maps. The whole genome comparison of AR CrossB10 to the reference genome of M4 revealed a few chromosomal rearrangements. The genetic linkage map and the new AR CrossB10 genome sequence are valuable tools for gene cloning in P. tritici-repentis.